Does crystallinity of extracted bone mineral increase over storage time? - William Querido; Andre L. Rossi; Andrea P. C. Campos; Alexandre M. Rossi; Marcos Farina (Materials Research, 2013)
It was recently shown that the crystallinity of extracted bone mineral samples from the fin bones of zebrafish could increase over storage time. This would have implications in many studies in which the samples need to be stored until analysis. The aim of this study was to further evaluate if the crystallinity of extracted bone mineral increases over storage time. The extracted mineral was a biological bone-like apatite produced in osteoblast cell cultures. The overall characterization of the mineral was done by energy dispersive X-ray spectroscopy, Fourier transform infrared spectroscopy, and high-resolution transmission electron microscopy. In order to evaluate possible changes in crystallinity over storage time, the same sample was analyzed by X-ray diffraction immediately after mineral extraction and after 18 months of storage. In conclusion, no statistically relevant changes were observed over storage time, although the occurrence of a slight increase in crystallinity could be discussed in the stored mineral sample.